2021
DOI: 10.1007/s42853-021-00085-y
|View full text |Cite
|
Sign up to set email alerts
|

How Profitable and Energy-Efficient Is Nepal’s Crop Production? A Case Study of Spring Rice Production in Jhapa District

Abstract: Purpose We investigated the energy usage, economics, and global warming potential (GWP) of spring rice production via farm sizes in Nepal. Methods Seventy farmers were selected via purposive sampling methods, and data were collected by interviewing the farmers on site. Results It was found that 22,987 mega joules of energy per hectare (MJ/ha) was invested in order to yield 77,355 MJ/ha worth of outputs (5262 kg/ha). The analysis shows that the highest share of energy input was contributed by machinery (33.50%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…In addition, the study also found that the energy used for the production of 1 t of crop was at a maximum in the case of mustard. A similar study in the Jhapa district of Nepal showed that the energy used in the production of monsoon rice was approximately 23,000 MJ ha⁻¹ compared to 22,800 MJ ha⁻¹ in this research (Paudel et al, 2021). Jhapa has similar socioeconomic and climatic parameters with the chosen project location in this study.…”
Section: Energy Use For Agricultural Productionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, the study also found that the energy used for the production of 1 t of crop was at a maximum in the case of mustard. A similar study in the Jhapa district of Nepal showed that the energy used in the production of monsoon rice was approximately 23,000 MJ ha⁻¹ compared to 22,800 MJ ha⁻¹ in this research (Paudel et al, 2021). Jhapa has similar socioeconomic and climatic parameters with the chosen project location in this study.…”
Section: Energy Use For Agricultural Productionsupporting
confidence: 58%
“…23,000 MJ ha⁻¹ compared to 22,800 MJ ha⁻¹ in this research (Paudel et al, 2021). Jhapa has similar socio‐economic and climatic parameters with the chosen project location in this study.…”
Section: Resultsmentioning
confidence: 41%